The Evaluation Methods of Decorative Concrete Horizontal Surfaces Quality - Albertas KLOVAS; Mindaugas DAUKŠYS (Medžiagotyra, 2013)
The main aim of this article was to determine blemishes of concrete surfaces and divide those surfaces according to following methods provided by two documents and by authors proposed image scanning method - “ImageJ”. The first method was CIB Report No. 24 “Tolerances on blemishes of concrete”. This method enables to evaluate concrete surfaces according to their visual appearance by using certain reference cards. The second method was GOST 13015.0-83. This method enables to evaluate the concrete surfaces according to their biggest dimension of the blemishes. The third, authors proposed, method was “ImageJ”. Latter method is based on the free source computer program. It helps to establish the quantity and the dimensions of the blemishes in the desired scale. Authors suggested to imply a ration between blemishes area and the all specimen’s area as a factor for evaluation of concrete surface quality. Three different concrete compositions were made: BA1, BA7 and BA8. Also, five different formworks were used: wood impregnated with polymeric oil [WPO], wood covered with rubber [WCR], sawn timber [ST], metal [M] and plastic [P] formworks. Following parameters of the obtained results were calculated: mean value, dispersion, standard deviation and the coefficient of variation. Also maximum and minimum values of experimental results are given. Intervals of the experimental results are provided for each specimen with the biggest possibility. DOI: http://dx.doi.org/10.5755/j01.ms.19.3.2006